If you've seen one, you've seen the mall : Europeans and American mass culture - Kroes, Rob (Univ. of Illinois Press, 1996)
The Dutch scholar Rob Kroes argues that American culture is "modular," continually fragmenting, disassembling, and reassembling itself - and in the process creating something new. In a series of topical essays that show why he is one of Europe's leading authorities on American culture, Kroes probes trends in American advertising, the image of the Vietnam war in American films, the implications of American vernacular culture as represented in rap music, and other topics.